Exosomal MicroRNAs in Serum as Potential Biomarkers for Ectopic Pregnancy - Sun, Jianhua (Biomed Res Int, 2020)
DESIGN: From July 2016 to June 2018, 36 women with symptomatic early pregnancy around 4-8 weeks of gestation were recruited into the study. Among them, there were 16 women with viable intrauterine pregnancy (VIP), 9 women with spontaneous abortion (SA), and 11 women of EP. Serum exosomal miRNAs were extracted and measured at the first prenatal visit. Statistical analysis was performed to determine the clinical utility of these biomarkers as single markers and as multimarker panels for EP. RESULTS: Concentrations of miR-378d in serum exosomes were significantly higher in EP than in VIP and also SA group. As a single marker, miR-378d had the highest specificity of 64% at the sensitivity of 89.1%. Comparatively, both combined panels of hCG, progesterone, miR-100-5p and hCG, progesterone, and miR-215-5P yielded the specificity of 96%. Panels for all markers achieved the highest specificity of 80% at the sensitivity of 91%. CONCLUSIONS: Although further validation in large-scale prospective studies is necessary, our results suggest that serum exosomal miR-378d, miR-100-5p, and miR-215-5P are promising biomarkers for early EP.